Embracing social procurement: an institutional work perspective on implementation in procurement practices - Chikwana, Josephine; Alinaghian, Leila; Razmdoost, Kamran (European Operations Management Association (EurOMA), 2024)
Organisations are increasingly using their purchasing power to create social value, a practice known as social procurement. This involves adapting existing procurement practices to incorporate social norms and practices. However, this process can lead to tensions and conflicts, requiring organisations to balance the priorities of different procurement practices. This study uses an institutional work lens to examine how organisations change and alter existing practices to navigate the complexity of integrating social procurement and traditional procurement practices. An analysis of six case studies reveals that organisations use various strategies of institutional work, which are influenced by contextual factors.
Keywords: Social Procurement; Institutional Change; Institutional Work